At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve the following system of equations:

[tex]\[
\left\{
\begin{array}{l}
6x + y - z = 14 \\
4x + 2y - z = 13 \\
x + 2y + 4z = 12
\end{array}
\right.
\][/tex]


Sagot :

Certainly! Let's solve the given system of linear equations step-by-step. The system of equations is:

[tex]\[ \left\{ \begin{align} 6x + y - z &= 14 \\ 4x + 2y - z &= 13 \\ x + 2y + 4z &= 12 \end{align} \right. \][/tex]

Here's how we would solve it:

1. Label the equations for reference:
[tex]\[ \begin{align*} (1) \quad 6x + y - z &= 14 \\ (2) \quad 4x + 2y - z &= 13 \\ (3) \quad x + 2y + 4z &= 12 \end{align*} \][/tex]

2. First, we will eliminate [tex]\( z \)[/tex] from the first two equations:
Subtract equation (2) from equation (1):
[tex]\[ (6x + y - z) - (4x + 2y - z) = 14 - 13 \][/tex]
[tex]\[ 6x + y - z - 4x - 2y + z = 1 \][/tex]
[tex]\[ 2x - y = 1 \quad \Rightarrow \quad (4) \][/tex]

3. Next, we will eliminate [tex]\( y \)[/tex] from equations (3) and (2):
Multiply equation (3) by 2 and subtract equation (2) from it:
[tex]\[ 2(x + 2y + 4z) - (4x + 2y - z) = 2 \cdot 12 - 13 \][/tex]
[tex]\[ 2x + 4y + 8z - 4x - 2y + z = 24 - 13 \][/tex]
[tex]\[ -2x + 2y + 9z = 11 \quad \Rightarrow \quad (5) \][/tex]

4. Now solve equations (4) and (5) together:
Equation (4):
[tex]\[ 2x - y = 1 \][/tex]
Equation (5):
[tex]\[ -2x + 2y + 9z = 11 \][/tex]
Add equations (4) and (5) to eliminate [tex]\( x \)[/tex]:
[tex]\[ (2x - y) + (-2x + 2y + 9z) = 1 + 11 \][/tex]
[tex]\[ y + 9z = 12 \quad \Rightarrow \quad (6) \][/tex]

5. Solve for [tex]\( y \)[/tex] in terms of [tex]\( z \)[/tex] using Equation (6):
[tex]\[ y = 12 - 9z \quad \Rightarrow \quad (7) \][/tex]

6. Substitute [tex]\( y \)[/tex] from Equation (7) into Equation (4):
[tex]\[ 2x - (12 - 9z) = 1 \][/tex]
[tex]\[ 2x - 12 + 9z = 1 \][/tex]
[tex]\[ 2x + 9z = 13 \][/tex]
[tex]\[ x = \frac{13 - 9z}{2} \quad \Rightarrow \quad (8) \][/tex]

7. Substitute [tex]\( x \)[/tex] and [tex]\( y \)[/tex] in terms of [tex]\( z \)[/tex] into one of the original equations, say Equation (3):
[tex]\[ x + 2y + 4z = 12 \][/tex]
Substitute [tex]\( x \)[/tex] from Equation (8) and [tex]\( y \)[/tex] from Equation (7):
[tex]\[ \left(\frac{13 - 9z}{2}\right) + 2(12 - 9z) + 4z = 12 \][/tex]
[tex]\[ \left(\frac{13 - 9z}{2}\right) + 24 - 18z + 4z = 12 \][/tex]
[tex]\[ \frac{13 - 9z}{2} + 24 - 14z = 12 \][/tex]
Multiply everything by 2 to clear the fraction:
[tex]\[ 13 - 9z + 48 - 28z = 24 \][/tex]
Combine like terms:
[tex]\[ 61 - 37z = 24 \][/tex]
[tex]\[ 37z = 37 \][/tex]
[tex]\[ z = 1 \][/tex]

8. Now, substitute [tex]\( z = 1 \)[/tex] back into Equation (7) to find [tex]\( y \)[/tex]:
[tex]\[ y = 12 - 9(1) = 3 \][/tex]

9. Finally, substitute [tex]\( z = 1 \)[/tex] into Equation (8) to find [tex]\( x \)[/tex]:
[tex]\[ x = \frac{13 - 9(1)}{2} = \frac{13 - 9}{2} = 2 \][/tex]

The solution to the system of equations is:
[tex]\[ (x, y, z) = (2, 3, 1) \][/tex]

So the values are:
[tex]\[ x = 2, \quad y = 3, \quad z = 1 \][/tex]